The contribution of customized lessons with cultural content in the learning of EFL among undergraduates - Oviedo Gómez, Hans Humberto; Álvarez Guayara, Henry Alberto (Colombian Applied Linguistics Journal, 2019)
This qualitative descriptive action research study explores the contribution of customized lessons with cultural content in the learning of English as a Foreign Language (EFL).. This study was conducted with a group of 17 undergraduates from the English Language Teaching (ELT) program at a state university in south-eastern Colombia. Data were collected via students’ artefacts (EFL lessons developed by the participants) with corresponding selfassessment, teachers’ field notes, and surveys on students’ perceptions. Findings suggest that designing customized lessons anchored in principles of second language acquisition results in more effective language learning. Additionally, using cultural content in the lessons makes communication more meaningful as undergraduates develop cultural knowledge and understanding. Finally, addressing learning styles and providing learning strategies in the lessons greatly contribute to EFL learning among undergraduates.